Human Milk Drives the Intimate Interplay Between Gut Immunity and Adipose Tissue for Healthy Growth - van den Elsen, Lieke W. J.; Verhasselt, Valerie (Frontiers in Immunology, 2021)
As the physiological food for the developing child, human milk is expected to be the diet that is best adapted for infant growth needs. There is also accumulating evidence that breastfeeding influences long-term metabolic outcomes. This review covers the potential mechanisms by which human milk could regulate healthy growth. We focus on how human milk may act on adipose tissue development and its metabolic homeostasis. We also explore how specific human milk components may influence the interplay between the gut microbiota, gut mucosa immunity and adipose tissue. A deeper understanding of these interactions may lead to new preventative and therapeutic strategies for both undernutrition and other metabolic diseases and deserves further exploration.